2020
DOI: 10.1177/0095798420931653
|View full text |Cite
|
Sign up to set email alerts
|

Parenting Together: Understanding the Shared Context of Positive Parenting Among Low-Income Black Families

Abstract: This study examined the relations between family demographics and positive parenting dimensions among urban-residing, low-income, Black caregiving dyads. Participants were 100 co-caregivers affiliated with a Head Start program and reporting on 50 preschool-aged children. Given that the parenting context for the caregiver pairs was not independent, multilevel dyadic analysis was employed to determine demographic predictors of positive parenting dimensions as measured by the emically derived Black Parenting Stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 60 publications
2
8
0
Order By: Relevance
“…This aligns with substantial evidence that Black parents' use proactive racial socialization strategies to protect their children from the deleterious influence of racial discrimination (Doyle et al, 2015;Wang et al, 2020;White-Johnson et al, 2010). Consistent with a growing number of studies (Elmore & Gaylord-Harden, 2013;Lozada et al, 2022;McWayne et al, 2020), we found that Black mothers valued parenting practices that focused on building their children's emotional and social well-being. The mothers considered emotional well-being a necessary component of supporting their children's freedom because it would better enable them to reject the types of dehumanizing ideologies (i.e., white supremacy, patriarchy, and homophobia) that might limit their sense of respect and self-worth.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…This aligns with substantial evidence that Black parents' use proactive racial socialization strategies to protect their children from the deleterious influence of racial discrimination (Doyle et al, 2015;Wang et al, 2020;White-Johnson et al, 2010). Consistent with a growing number of studies (Elmore & Gaylord-Harden, 2013;Lozada et al, 2022;McWayne et al, 2020), we found that Black mothers valued parenting practices that focused on building their children's emotional and social well-being. The mothers considered emotional well-being a necessary component of supporting their children's freedom because it would better enable them to reject the types of dehumanizing ideologies (i.e., white supremacy, patriarchy, and homophobia) that might limit their sense of respect and self-worth.…”
Section: Discussionsupporting
confidence: 88%
“…First, we underscored the importance of examining Black mothers' beliefs and practices as a joint function of multiple individual and contextual characteristics (i.e., ages of their children, their personal experiences as a child, and the availability of caregiving networks). We must continue to consider the complex relations between Black parents' social identities (i.e., ethnicity, gender, and social class location), and their caregiving contexts as we theorize and empirically study parenting (McWayne et al, 2020). Second, we highlighted the importance of attending to concepts such as hope, love, and joy, as an overlooked area of research within empirical research on Black family processes.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
See 2 more Smart Citations
“…One additional task of Black families is preparing their children for discrimination and racism. While there is a large focus in the research on negative parenting practices in Black families, the extant scholarship on positive parenting indicates that these practices influence children in the domains of socioemotional (i.e., maternal warmth, empathy, and communication), spiritual, academic well-being, and ethnic identity (McWayne et al, 2020). Other aspects of family relationships that appear to be important in Black families include having close and flexible family relationships, family cohesion, and support (Pollock et al, 2015).…”
Section: Maternal Caregiving Within Black Communitiesmentioning
confidence: 99%